2021
DOI: 10.3389/fpubh.2021.693159
|View full text |Cite
|
Sign up to set email alerts
|

Fibromyalgia in Health Care Worker During COVID-19 Outbreak in Saudi Arabia

Abstract: Background: In the face of the contemporary COVID-19 pandemic, health service providers have emerged as the most at-risk individuals who are likely to contract the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2).Aim: To measure the prevalence of fibromyalgia (FM) during COVID outbreak among health workers in Saudi Arabia using FiRST and LFESSQ tool.Methods: The study employed a cross-sectional methodology to explore the prevalence of Fibromyalgia among health workers at different health care setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Although no study on myofascial pain syndrome after the pandemic exists, we could refer to studies on fibromyalgia, as they share a similar disease entity. In a survey conducted in Saudi Arabia, the prevalence of fibromyalgia in health workers was high (12.6–19.8%) during the pandemic [ 21 ]. However, respondents were mostly in their 40s, and the study only evaluated the early stage of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Although no study on myofascial pain syndrome after the pandemic exists, we could refer to studies on fibromyalgia, as they share a similar disease entity. In a survey conducted in Saudi Arabia, the prevalence of fibromyalgia in health workers was high (12.6–19.8%) during the pandemic [ 21 ]. However, respondents were mostly in their 40s, and the study only evaluated the early stage of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…28 With respect to work, a study conducted in 2020 in Saudi Arabia found a high prevalence of fibromyalgia sufferers among healthcare workers. 29 The frontline healthcare workers for COVID-19 had to deal directly with an overload of work, being drastically affected by emotional stress, causing depression and anxiety. 30 These factors are related to the management of fibromyalgia and, as previously mentioned, with a high frequency in the group severely impacted by the syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Two articles were published in 2022 [20,21], three articles were published in 2021 [18, 19,25], one article was published in 2019 [22], one article was published in 2018 [24], and one article was published in 2006 [23]. The studies were conducted in different places in Saudi Arabia, as follows: Taif city [21], outpatient clinics and the daycare unit in a tertiary care hospital in south-western Saudi Arabia [20], different hospitals in Saudi Arabia [19], a non-pro t professional Saudi pharmaceutical society [18], King Abdulaziz University [25], the rheumatology department of Al-Ameen Hospital in Taif [22], a single academic institution in Riyadh [24], and a teaching hospital in Jeddah [23]. All studies were cross-sectional in design except two, which were retrospective [20,23].…”
Section: Characteristics Of the Included Articlesmentioning
confidence: 99%